2010
DOI: 10.1016/j.biomaterials.2010.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte-based human tissue engineered vascular grafts

Abstract: The success of small-diameter tissue engineered vascular grafts (TEVGs) greatly relies on an appropriate cell source and an efficient cellular delivery and carrier system. Pericytes have recently been shown to express mesenchymal stem cell features. Their relative availability and multipotentiality make them a promising candidate for TEVG applications. The objective of this study was to incorporate pericytes into a biodegradable scaffold rapidly, densely and efficiently, and to assess the efficacy of the peric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 35 publications
3
127
0
1
Order By: Relevance
“…Despite an intact immune system, implants were not rejected, supporting the notion that MSCderived implants are less immunogenic, perhaps due to the secretion of anti-inflammatory factors (He et al, 2010). It was suggested that pericytes reduce obstruction in vascular grafts and show promise for use in arterial conduits (He et al, 2010).…”
Section: Vascularisationmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite an intact immune system, implants were not rejected, supporting the notion that MSCderived implants are less immunogenic, perhaps due to the secretion of anti-inflammatory factors (He et al, 2010). It was suggested that pericytes reduce obstruction in vascular grafts and show promise for use in arterial conduits (He et al, 2010).…”
Section: Vascularisationmentioning
confidence: 92%
“…Cultured flow cytometry-sorted pericytes from human skeletal tissue (CD146/NG2/PDGFRβ+, CD45/CD56/CD34-) seeded onto poly(esterurethane) urea (PEUU) scaffolds have been used to create small-diameter tissue engineered vascular grafts (TEVG) (He et al, 2010). Following implantation, TEVG displayed vascular remodelling as evidenced by collagen and elastin deposition, as well as the presence of αSMA and calponin (He et al, 2010).…”
Section: Vascularisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our novel findings above on the perivascular behavior of DFAT cells were consistent to the new understandings of MSCs. Recent studies identified that pericytes in multiple organs and tissues could demonstrate perivascular markers (CD146, NG2 and CD140b) and MSCs markers (CD44, CD73, CD90, CD105), exhibiting osteogenic, chondrogenic and adipogenic potentials [55][56][57]. MSCs within adult mesenchymal tissues such as bone and adipose also could differentiate into or act as pericytes without induction of growth factors [58][59].…”
Section: Angiogenesismentioning
confidence: 99%
“…With static culture techniques, the transportation of oxygen, nutrients, and low-molecular-weight metabolites is limited by diffusion preventing cells from being able to survive in the scaffold interior. To overcome this problem, a variety of dynamic culture systems have been used including perfusion bioreactors [45,56], spinner flasks [32,58], roller bottles [26], and rotating wall bioreactors [55,59]. The high-aspect ratio vessel (HARV) bioreactor is a low-shear, high-mass transfer system that improves cell-seeded bone tissue-engineering scaffold performance [6,9,60].…”
Section: Introductionmentioning
confidence: 99%